Edukasi Masyarakat Mengenai Pemanfaatan Garam Dapur (NaCl) Dalam Mengurangi Kadar Asam Sianida Pada Ubi Kayu - Nuri Yanti (Khidmah, 2022)
Cassava in addition to containing nutrients and carbohydrates as a source of calories and contains several compounds that are useful for the body, cassava also contains cyanogenic glucoside compounds which are toxic and can form cyanide acid. The potential toxicity of cyanide depends on the level of cyanide which is toxic to humans. Reduction of cyanide acid levels can be done by processing by immersing NaCl. NaCl is able to dissolve cyanide acid, where one of the properties of cyanide acid is easy to react with NaCl in the immersion process. The purpose of this activity is to increase public knowledge about the use of table salt to reduce cyanide toxicity in cassava. The method used in this community outreach is by distributing leaflets, giving pretest questions and providing explanations to the community regarding the material to be given and then evaluating the results of the community service that has been carried out. The results of community service showed that there was an increase in public knowledge about the benefits of using table salt in reducing cyanide in cassava